Relationship Between Community Behavior And Dengue Hemorrhagic Fever Incidence - Astuti, Bunga Harum; Marsanti, Avicena Sakufa; Abidin, Zaenal (Politeknik Kesehatan Kemenkes Mamuju, 2024)
According to DHF incidence data obtained from the Madiun City Health Profile, there were 48 cases and one death in 2021, an increase in cases of 212 cases with one death in 2022, and there were still 144 cases with one death in 2023. The purpose of this study is to determine the relationship between community behavior and the incidence of dengue hemorrhagic fever in the Manguharjo Health Center Working Area, Madiun City. This study has used quantitative research with a case-control research design. The study population was all dengue hemorrhagic fever patients recorded in medical records in Winongo and Nambangan Lor Villages with a period of January 2023-16 February 2024, totaling 29 cases. The sample used was 54 respondents, with 27 cases and 27 controls. The sampling technique used was purposive sampling, with the inclusion criteria of the case being that the patient had suffered from DHF disease, while the exclusion criteria were that the patient moved residence when the study was conducted. The Data analysis used was a univariate and bivariate analysis using the Chi-Square test. The results show that there is a relationship between the presence of hanging clothes p-value of 0.013 with an odds ratio of 5.091, there is no relationship between the distance from house to house p-value of 0.420 and an odds ratio of 2.841, and there a relationship between the implementation of eradication to prevent dengue fever transmission p-value of 0.029 and an odds ratio of 4.038. The variable with the highest risk for dengue hemorrhagic fever is the presence of hanging clothes. At the same time, the variable that has the most minor risk is the distance between houses. Therefore, it is expected that the Manguharjo Health Center can educate and counsel the community on implementing mosquito’s nest eradication to prevent transmission and minimize dengue cases.